Integration in large, related M&As: linkages between contextual factors, integration approaches and process dimensions. (26th July 2012) - Ellis, Kimberly M.; Weber, Yaakov; Raveh, Adi; Tarba, Shlomo Yedidia
The purpose of our study is to examine differences in contextual factors and process dimensions across three integration approaches used in large, related M&As – absorption, symbiotic and transformation. Absorption and symbiosis are commonly documented in M&A process literature and transformation, while emphasised less in existing M&A studies, appears to be widely utilised in large, related M&As. Using a unique co-plotting technique, we find that the existence of several contextual factors which influence the potential for resource combinations and use of multiple process dimensions which facilitate actual resource combinations during the implementation stage differ significantly depending upon the integration approach used by the combined firm. Moreover, our study adds to growing literature on the M&A process by providing systematic evidence of the important linkages between integration approaches, pre-existing contextual factors and process activities.